Jetsam on Flotsam: Notes on Material and other Remnants and Residues (Altre Modernità, 2020)
In an attempt to open a conversation on the remnant, this essay proceeds as a collection of notes on the following topics:1) Definitions of flotsam and jetsam2) Some famous figures of waste: Defoe, Melville, Twain, myth of Hercules, A.C. Bradley, Trotsky, Walter Benjamin3) Waste in contemporary fiction and media, with readings of some touchstone passages4) Found materials and residues as subjects in the visual arts5) Two final images of flotsamUnderlying the discussion of these particulars are three themes based on common reactions to remnants, waste, trash, flotsam and jetsam: devastation, abjection, and bricolage.